Review Note on Hermite-Hadamard Type Integral Inequality ViaRiemann-Liouville Fractional Integral Operators (Global Journal of Sciences, 2024)
In the context of fractional calculus, the concept of convexity is primarily used to tackle various challenges in both theoretical and applied research. This review paper aims to present Hermite–Hadamard (H-H) inequalities related to different classes ofconvex functions via Riemann-Liouville fractional integral operators.
Keywords: Preinvex functions; Hadamard inequality; Ψ-Riemann-Liouville Fractional Integral Oprator